A Systematic Literature Review of Research and Implication Blended Learning in Building Modern Education - Ariyatun Ariyatun; Sudarmin Sudarmin; Sri Wardani; Sigit Saptono (Universitas Negeri Semarang, 2022)
This study attempts to present a thorough picture of how blended and mixed learning are used to promote meaningful learning at the secondary and higher education levels. To synthesize academic research pertaining to the use of blended learning in education, a systematic review of the literature was conducted. 50 articles out of a total of 1409 that were screened met the requirements for inclusion. The findings point to a number of beneficial roles in constructing modern education at the secondary and postsecondary levels. The effects of blended learning have a significant impact on improving how students engage with low-tech infrastructure while studying. In the new norm, teachers must be at the center of more efficient decision-making on blended learning. This paper's content can be used to describe the mixed-methods trend in education and how it helps to provide engaging learning opportunities.